Running on Empty. - Lahti, Chirstine; Hirsch, Judd.; Plimpton, Martha; Phoenix, River; Hill, Steven; Warner Home Video (Burbank, CA Warner Home Video, 1988)
After antiwar activists blew up a napalm lab in 1971, they became lifelong fugitives. They and their children stay one step ahead of the law by moving from state to state, identity to identity. But now their elder son wants to stop running from a past that is not his.
Directed by Sidney Lumet.
Christine Lahti, Judd Hirsch, Martha Plimpton, River Phoenix, Steven Hill.
MPAA rating PG 13.
Closed captioned.
Los Angeles Firm Critics Best Actress was awarded to Cristine Lahti and the Best Supporting Actor by the National Borad of Review was awarded to River Phoenix
109074
Keywords: Anti-war - activists. -- DVD -- Fiction. -- United States; Family. -- Parent and child relationships; Law evasion